Sainte Mélanie et les reliques des martyrs - Laurence, P. (Liber Annuus, 2001)
Abstract When he wrote, “The Life of St. Melanie”, Gerontios did not refrain from mentioning the diverse circumstances in which, all along her existence, this great lady of the 5th century, converted to the monastic way of life, shows her fervor towards the martyrs and their cult. St. Melanie placed them at the center of the monasteries she had built for her monks and nuns of Jerusalem. This form of piety, bound to a period of time in a way particularly notable, is presented as an additional witness to the Christian faith of this saint.